Diagnosis of Cellulitis in the Immunocompromised Host - Charles F Carey; Lawrence Dall (Canadian Journal of Infectious Diseases)
A prospective study of diagnostic techniques in cellulitis was performed on 28 patients with malignancy. Twenty-two (78%) of the fine needle aspiration cultures and 10 (35%) of the blood cultures were positive in this immunocompromised population. The incidence of positive fine needle aspiration cultures (P<0.005) or bacteremia (P<0.0005) was significantly higher than results obtained in an immunocompetent population with cellulitis at the same institution. Staphylococci or streptococci were recovered in 59% of positive cultures, while aerobic Gram-negative bacilli grew in 33%. This study indicates that in the immunocompromised population with cellulitis, fine needle aspiration and blood cultures should be obtained, and the antibiotic regimen should cover Gram-positive cocci and Gram-negative bacilli pending the results of cultures.